Cálculo y análisis de exponentes de geometría hidráulica para cauces de Colombia (2017)
"We performed a calculation of the b,f and m exponents of the at-a-station hydraulic geometry theory by Leopold & Maddock in 1953. According to this theory, the discharge of a stream in a hydrologic station may be related to its width, depth and mean flow velocity, with exponential relations. In relation with this, we took historic values of the mentioned variables from 70 hydrologic stations of the IDEAM (Institute of hydrology, meteorology and environmental studies). These data were up to 40 years old. From these, we performed exponential regressions and calculated the exponents for each of the width, depth and velocity relations (each with discharge as the dependent variable).These results yield the exponential relations that can describe the behavior of the river stretch in which the station is located. The results were plotted in ternary diagrams, where it is shown that the better results (in terms of dispersion and expected values) are obtained from the stations with higher quantity of data." -- Tomado del Formato de Documento de Grado.